(untitled) (Al-Mansour Journal, 2022)
In this paper, we study the concept of minimal topological spaces and its relation with first countable space, we prove that if X is first countable completely regular space, then the following are equivalent. • X is first countable and minimal completely regular space. • X is first countable and completely regular – closed space. A first countable and minimal Urysohn is semi regular and Let be a collection of a topological spaces and , then X is first countable and Hausdorff – closed if and only if each x(n) is first countable and Hausdorff – closed